(3JfXje egfI GdeMGSHI aj GdLRGFQs - (3HQGgej(B, (3ahRjIs; (3MOjOj, BOes ((3GdLRGFQs (3OGQ GdHGMK ddfTQ hGdGTgGQs, 2021)
(3jMJhj gPG GdcJGH Ydi aUdjf eJJGdjjf, MjK JWQb GdcGJH aj GdaUd GdChd ddGWGQ GdfXQj hGdJfXjej degfI GdeMGSHI, YehejGJ Mhd GdeMGSHI eY eHGOF hbhGYO GdSdhc hCNdGbjGJ egfI GdeMGSHIhJfXjegG, hHYOgd PcQ dfG aj GdaUd GdKGfj JfXje egfI GdeMGSHI aj GdLRGFQ eY GdJWhQ GdJGQjNj dJTQjYGJgG,cPdc GdJWhQ GdJGQjNj degfI GdeMGSHI, hGJLGgGJgG aj GdLRGFQ aj Xd GdGUdGMGJ GdeMGSHjI, hOhGaY GdGUdGM GdeMGSHj, hcPdc GdgjFGJ GdeTQaI Ydi JfXje egfI GdeMGSHIaj GdLhGFQ(B.s
Keywords: (3GdeMGSHIs